Ciliated Hepatic Foregut Cyst: A Report of a Case Incidentally Discovered during Transplant Evaluation - Thomas Enke; Wuttiporn Manatsathit; Shaheed Merani; Kurt Fisher (Case Reports in Gastrointestinal Medicine)
Ciliated hepatic foregut cyst (CHFC) is a rare benign cyst of the liver derived from an embryonic remnant of foregut epithelium. CHFC is typically asymptomatic and is found incidentally. Recent reports of malignant transformation may warrant surgical removal of CHFC. We present the case of a 54-year-old male who was discovered to have a CHFC while undergoing kidney transplant evaluation.